PENGEMBANGAN KAWASAN AGROWISATA BBI LUBUAK MINTURUN SEBAGAI DESTINASI UTAMA PARIWISATA SUMATERA BARAT (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2013)
This research focuses on community social economic attraction in agrotourism BBI Lubuk Minturun of West Sumatra region. The method is regional economic approach with tool analyses are location quotient, shift share analysis, and travel cost method to determine integrating linkages of community economic activities in the region. This research shows, first: Padang tourism attraction potency as National activitiy center (PKN) in PP No: 50 year 2011 about National tourism masterplan included in national tourism destination (DPN) together with Bukittinggi. Furthermore, in West Sumatra tourism masterplan, Padang has become Province tourism destination region (DPP) with its strategic destination region (KSPP) are Pesisir Selatan, Padang Pariaman and its potential region is Pariaman city. In the case as DPN, DPP of Padang city has wide tourism potential, approximately 169 tourism destinations to attract foreign and national tourist to visit and spend their leisure time. Second: Kuranji district zone has the highest travel cost on average outside Koto Tangah district in amount of 170,783 rupiahs, in the other hand Bungus Teluk Kabung district has the lowest travel cost is 120,877 rupiahs. The high average travel cost to BBI Lubuk Minturun is determined by average visit per year per person. The highest consumer surplus is at Koto Tangah district zone attain 99,875.23 rupiahs and the lowest is Teluk Kabung district zone. Furthermore, the lowest average costs based on origin visit zone are Agam, Lima Puluh Kota, and west Pasaman destination.